Navigating Non-Tariff Barriers: Strategic Approaches to Indonesian Halal Product Exports in the Middle East - Abu Hasan; Dwi Alifatul Rulliana; Eka Putri Lestari; Dwi Agustin; Salsabila Auliya; Putri Catur Ayu Lestari (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2026)
The global halal industry has emerged as a strategic sector in international trade, offering significant opportunities for Indonesia as the country with the largest Muslim population in the world. Despite its substantial production potential, the performance of Indonesian halal product exports to Middle Eastern markets remains constrained by various non-tariff barriers. This study aims to analyze the dynamics of non-tariff barriers and identify strategic approaches adopted to strengthen Indonesian halal product exports to the Middle East. A qualitative research design employing content analysis was used to examine data collected from policy documents, academic literature, industry reports, and media publications related to halal trade and export activities. The findings indicate that non-tariff barriers are primarily manifested through differences in halal certification standards, technical regulations, sanitary and phytosanitary requirements, and complex administrative procedures. These barriers increase compliance costs, prolong export processes, and reduce the competitiveness of Indonesian halal products in international markets. The study also reveals that Indonesian exporters, particularly Micro, Small, and Medium Enterprises (MSMEs), face significant challenges related to certification harmonization, regulatory understanding, and financial capacity. To address these challenges, the government and business actors have implemented several strategic initiatives, including halal diplomacy through Mutual Recognition Arrangements (MRA), strengthening domestic halal certification institutions, providing technical assistance and export training programs, and expanding international trade promotion activities. The study concludes that non-tariff barriers function not only as regulatory constraints but also as critical determinants of export competitiveness. Therefore, greater harmonization of halal standards, enhanced international cooperation, and continuous capacity development are essential for improving the position of Indonesian halal products in Middle Eastern markets.